Combating corruption while respecting human rights : a critical study of the non-conviction based assets recovery mechanism in Kenya and South Africa - Obura, Ken Otieno (Rhodes University, Faculty of Law, Law, 2014)
The thesis contributes to the search for sound anti-corruption laws and practices that are effective and fair. It argues for the respect for human rights in the crafting and implementation of anti-corruption laws as a requisite for successful control of corruption. The basis for this argument is threefold: First, human rights provide a framework for checking against abuse of state's police power, an abuse which if allowed to take root, would make the fight against corruption lose its legitimacy in the eye of the people. Second, human rights ensure that the interest of individuals is catered for in the crafting of anti-corruption laws and practices thereby denying perpetrators of corruption legal excuses that can be exploited to delay or frustrate corruption cases in the courts of law. Third, human rights provide a useful framework for balancing competing interests in the area of corruption control "“ it enables society to craft measures that fulfils the public interest in the eradication of corruption while concomitantly assuring the competing public interest in the protection of individual members' liberties "“ a condition that is necessary if the support of the holders of these competing interests is to be enlisted and fostered in the fight against corruption. The thesis focuses on the study of the non-conviction based assets recovery mechanism, a mechanism that allows the state to apply a procedure lacking in criminal law safeguards to address criminal behaviour. The mechanism is thus beset with avenues for abuse, which if unchecked could have debilitating effects not only to individual liberties but also to the long term legitimacy of the fight against corruption. In this regard, the thesis examines how the human rights framework has been used in Kenya and South Africa to check on the potential dangers of the non-conviction based mechanism and to provide for a proportional balance between the imperative of corruption control and the guarantee against arbitrary deprivation of property. The aim is to unravel the benefits of respecting human rights in the fight against corruption in general and in the non-conviction based assets recovery in particular. Kenya and South Africa are chosen for study because they provide two models of non-conviction based mechanisms with different levels of safeguards, for comparative consideration.
Keywords: Human rights -- Kenya; Human rights -- South Africa; Corruption -- Kenya; Corruption -- South Africa; Reparation (Criminal justice) -- Kenya; Reparation (Criminal justice) -- South Africa; Political corruption -- Kenya; Political corruption -- South Africa; Corruption investigation -- Kenya; Corruption investigation -- South Africa